(3aGYdjGJ JOQjS GdQjGVjGJ aj YUQ GdeYdheGJjIs - (3eLOj YRjR(B, (3EHQGgjes ((3GdbGgQI(B:s (3YGde GdcJH(B,s, 2002)
(3GdQjGVjGJ aj GddZI hGddZI aj GdQjGVjGJ,GdQjGVjGJ hGdadSaI,GdQjGVjGJ aj Ref JOQjS Ref GdeVGQY GdJGe HGddZI GdGfLdjRjI,JOQjS GdgfOSI ddJdGejP HWjF GdJYdje HGSJNOGe CSdhH Md GdeTcdGJ,GdOGdI ceaghe QjGVjs
(3HHdjhZQGajG(B:(3U(B.191s
Keywords: (3GdQjGVjGJs